Geodynamics of formation of emergency situation of a building resulting from a subway construction - Sadovenko I. O.; Zahrytsenko A. M.; Dereviahina, N. І.; Onyshchenko S. V. (НТУ «ДП», 2024)
The analysis is based on a range of available data, including visual inspections of the deformation observed in a hostel building, with photographic documentation of subsidence at the corner section. It also incorporates an inspection of the building's basement, year-long observations of the surrounding area prior to the incident, and confirmation of the absence of suffusion soil loosening under the building or nearby areas before the emergency. Additional data includes evidence of loess slurry accumulation in a ditch excavated on the sidewalk opposite the Dnipro University of Technology's educational building and findings from engineering and geological investigations.
Keywords: Geodynamics